Biochar as a filler in mixed matrix materials: Synthesis, characterization, and applications. Issue 41 (31st May 2019) - Lewis, Jeremy; Miller, Mark; Crumb, Jake; Al‐Sayaghi, Maram; Buelke, Chris; Tesser, Austin; Alshami, Ali
ABSTRACT: The use of mixed‐matrix materials (MMM) has become a major topic of research in recent years, due to unique properties achieved in these composites. In this work, biochar from sunflower seed hull pyrolysis and biochar/polysulfone (PSF) MMMs were produced and characterized. The optimal pyrolysis temperature for biochar production was determined to be 500 °C. The resulting biochar properties were an iodine number of 203 mg/g and a pore volume of 0.595 mL/g. In MMM fabrication, the use 4% ethanol as nonsolvent in the wet phase inversion process increased the glass transition temperature by 8 °C, indicating improved biochar/PSF interaction. The presence of biochar was shown to create pores in otherwise dense surfaces. The critical surface energy was also increased by the addition of biochar from 28.6 mN/m in pristine PSF to 35.7 mN/m in biochar/PSF MMMs. We identified and discussed several potential applications based on the determined properties. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48027. Abstract :